Equilíbrios no Terror: Trabalho forçado, fuga e Continuidades clandestinas no Congo-Brazzaville, 1918-1968 - Alexander Keese (Cadernos de Estudos Africanos)
The end of concession company rule in the French Middle Congo in the 1920s – in many ways analogous to similar processes in the Portuguese colonies of Southern Africa – opened gates towards a less repressive set-up of local administration. However, this route was not taken. Until 1946, the Congo remained under the joint impact of various types of forced labour; after the 1946 reforms, the logics of compulsory labour survived in a less extensive variant and continued even after independence. This article analyses the balance on terror, and the strong reactions of local populations, namely in the western and northern part of the Congolese territory. Those populations responded to colonial violence with flight movements, and successfully undermined the pillars of the colonial state.